Step-by-step explanation:
33x
Answer:
The answer is;
4^3/10 • x^9/10 •y^3/5
Step-by-step explanation:
We want to express the expression in the bracket in radical form;
(4x^3y^2)^3/10
What we shall do here is to multiply all the powers of the terms in the bracket by 3/10
So we shall have;
4^3/10 • x^(3*3/10) * y^(2*3/10)
= 4^3/10 • x^9/10 • y^3/5
X = -2.1/3
I hope this helps
Step-by-step explanation:
√a is defined only when a >= 0.
Therefore for √4x * √(x + 2) to be defined, both 4x and x + 2 must be non-negative.
When 4x >= 0, x >= 0.
When x + 2 >= 0, x >= -2.
x >= 0 and x >= -2, therefore we have x >= 0. (D)
Dy/dx = y cos x
y = Ae^sin(x)
y(0) = Ae^sin(0) = A = 3
A = 3
Therefore, y = 3e^(sinx)